Identification of cellular signatures associated with chinese hamster ovary cell adaptation for secretion of antibodies - Ying Bai; Ivan Domenech Mercadé; Ramy Elgendy; Giulia Lambiase; Sew Peak-Chew; Catarina Franco; Steven W. Wingett; Tim J. Stevens; Luigi Grassi; Noah Hitchcock; Cristina Sayago Ferreira; Diane Hatton; et al. (Computational and Structural Biotechnology Journal)
The secretory capacity of Chinese hamster ovary (CHO) cells remains a fundamental bottleneck in the manufacturing of protein-based therapeutics. Unconventional biological drugs with complex structures and processing requirements are particularly problematic. Although engineered vector DNA elements can achieve rapid and high-level therapeutic protein production, a high metabolic and protein folding burden is imposed on the host cell. Cellular adaptations to these conditions include differential gene expression profiles that can in turn influence the productivity and quality control of recombinant proteins. In this study, we used quantitative transcriptomic and proteomic analyses to investigate how biological pathways change with antibody titre. Gene and protein expression profiles of CHO cell pools and clones producing a panel of different monoclonal and bispecific antibodies were analysed during fed-batch production. Antibody-expressing CHO cell pools were heterogeneous, resulting in few discernible genetic signatures. Clonal cell lines derived from these pools, selected for high and low production, yielded a small number of differentially expressed proteins that correlated with productivity and were shared across the biotherapeutics. However, the dominant feature associated with higher protein production was transgene copy number and the resulting mRNA expression level. Moreover, variability between clonal cell lines suggested that the process of cellular adaptation is variable with diverse cellular changes associated with individual adaptation events.